Upaya Peningkatan Literasi Keagamaan dan Sosial di Desa Lekopancing: Efforts to Increase Religious and Social Literacy in Lekopancing Village - Jahada Mangka; Muh. Fadel As'ad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The implementation of the Community Service Program (KKN) by STIBA Makassar in Lekopancing Village, Tanralili District, Maros Regency, aims to increase students' ability to integrate religious and general knowledge directly with the community, especially in areas that are still developing. This program also plays a role in supporting local governments in religious and social development as well as empowering families and communities through various educational, health and entrepreneurial activities. Implementation methods include religious activities such as village workshops or seminars, Islamic boarding schools, teaching in kindergartens/tpa, friendship, i'tikaf and evening prayers, social gatherings, imams and Friday sermons, tahsin Al-Quran, Clean Friday, as well as syar'iyya cupping and rukiah services. Based on SOAR observations, the success of the work program reached 95%, showing the effectiveness of student contributions in increasing literacy and religious knowledge in wider society as well as increasing social awareness. These results also reflect the important role of KKN in forming Muslim scholars who have noble character and are responsible for the progress of the people and nation.